Relationship between breakthrough cancer pain, background cancer pain and analgesic treatment - case series and review of the literature - Chrysanthi Batistaki; Michal Graczyk; Marcin Janecki; Agata Anna Lewandowska; Rita Moutinho; Kiriaki Vagdatli (BioExcel Publishing Ltd, 2022)
The assessment and treatment of breakthrough cancer pain (BTcP) remain a major challenge in medicine due to its high impact on several aspects of health-related quality of life. BTcP should be carefully monitored in all cancer care settings by a multidisciplinary team to provide an appropriate and personalized clinical approach. The aim of this paper is to provide healthcare professionals involved in cancer pain management with a review of the relevant literature on the relationship between background cancer pain and BTcP which, by definition, occurs despite adequately controlled background cancer pain. The clinical cases presented contribute to a better understanding of this issue and underline its impact in daily clinical practice. This article is part of the Management of breakthrough cancer pain Special Issue: https://www.drugsincontext.com/special_issues/management-of-breakthrough-cancer-pain